Гетерогенная плазма дугового разряда в магнитном поле; Известия вузов. Физика; Т. 60, № 7 - Мышкин В. Ф. Вячеслав Фёдорович; Тычи М. Милан; Хан В. А. Валерий Алексеевич; Беспала Е. В. Евгений Владимирович; Ленский В. Н. Владимир Николаевич; Гамов Д. Л. Денис Леонидович (2017, 2017)
Заглавие с экрана